Nightwing - Taylor, Tom 1978- (DC Comics, 2021)
Nightwing is back-and his drive to keep Blüdhaven safe has never been stronger! But his adoptive city has elected a new mayor with the last name Zucco. When Nightwing enlists Batgirl's help in investigating the politician bearing the same name as the man who murdered his parents, she unearths details that will shock and fundamentally change the hero. Dick Grayson's big heart has protected those persecuted by bullies in his youth, combated evil alongside Batman as Robin, and pledged his newly inherited wealth to enriching Blüdhaven as Nightwing. His kindness and generosity have always guided his life. But now a new villain stalks the back alleys, removing the hearts of the city's most vulnerable
"Nightwing created by Marv Wolfman & George Pérez.
Keywords: Nightwing -- (Fictitious character) -- Comic books, strips, etc; Robin, -- the Boy Wonder (Fictitious character) -- Comic books, strips, etc; Grayson, Dick -- Fiktive Gestalt; Nightwing / (Fictitious character) / Fiction; Superheroes / Fiction; Villains / Fiction; Young adult graphic novels; Graphic novels / Young adult fiction; Science fiction; Graphic novels; Bandes dessinées de superhéros; Comic; Comics (Graphic works); Superhero comics